Karantina sebagai Upaya Mengantisipasi Pandemi: Studi Komperatif terhadap Penafsiran Ibnu Katsir dan Imam Al Qurthubi pada QS Al-Baqarah: 243 - Balqis, Sabila Phutri; Nurfuadi, Wika; Andy, Safria (Ikatan Da'i Indonesia, 2023)
Recently, Indonesia experienced a pandemic that also occurred in all parts of the world. This causes unrest among the community. Quarantine is an effort made to minimize the development of a pandemic. Therefore, this effort is made to see how the Qur'an speaks in Q.S. Albaqarah verse 243.This thesis uses a type of library research (library qualitative), the analysis is descriptive analysis. After conducting research, it was found that Ibn Kathir in his time, the community at that time also faced a quarantine atmosphere because of the epidemic. Hence, the relevance of his thoughts in the interpretation of Ibn Kathir by reviewing the QS. Albaqarah 243 that once there was a pandemic in a village, then they left the village to get a long life. Then Allah swt took their life.From the reviews that the author read, Alqurthubi did not directly experienced the plague of his time, but Alqurthubi interpreted the QS. Albaqarah 243 as the word of Allah for fear of death Alqurthubi interprets with the cry of an angel, it is permissible to leave the area affected by the plague but not to escape from the plague. To interpret the verse, Alqurthubi does not deny interpreting the verse with the Qur'an, Hadith, and Ijtihad even though he did not experience the plague.Comparative studies on the assessments of Ibn Kathir and Alqurthubi have similarities in interpretation, only the explanation is different due to different times..